The arable ecosystem as battleground for emergence of new human pathogens - Van Overbeek, Leo; van Doorn, Joop; Wichers, Jan; van Amerongen, Aart; van Roermund, Herman; Willemsen, Peter (Frontiers in Microbiology, 2014)
Disease incidences related to Escherichia coli and Salmonella enterica infections by consumption of (fresh) vegetables, sprouts and occasionally fruits made clear that these pathogens are not only transmitted to humans via the ‘classical’ routes of meat, eggs and dairy products, but also can be transmitted to humans via plants or products derived from plants. Nowadays, it is of major concern that these human pathogens, especially the ones belonging to the taxonomical family of Enterobacteriaceae, become adapted to environmental habitats without losing their virulence to humans. Adaptation to the plant environment would lead to longer persistence in plants, increasing their chances on transmission to humans via consumption of plant-derived food. One of the mechanisms of adaptation to the plant environment in human pathogens, proposed in this paper, is horizontal transfer of genes from different microbial communities present in the arable ecosystem, like the ones originating from soil, animal digestive track systems (manure), water and plants themselves. Genes that would confer better adaptation to the phytosphere might be genes involved in plant colonization, stress resistance and nutrient acquisition and utilization. Because human pathogenic enterics often were prone to genetic exchanges via phages and conjugative plasmids, it was postulated that these genetic elements may be hold key responsible for horizontal gene transfers between human pathogens and indigenous microbes in agroproduction systems. In analogy to zoonosis, we coin the term phytonosis for a human pathogen that is transmitted via plants and not exclusively via animals.